Analyses of True-Triaxial Hydraulic Fracturing of Granite Samples for an Enhanced Geothermal System - Tao Zhang; Qinhong Hu; Wenyi Chen; Yang Gao; De Li; Xiating Feng (Lithosphere, 2022)
AbstractThe fracturing behavior of enhanced geothermal system (EGS) reservoirs merits investigation under field-relevant temperature and stress conditions, in order to understand the creation of an extensive fracture network that helps achieve a high heat exchange efficiency. In this work, hydraulic fracturing tests were conducted on two 300 mm sized cubic granite samples at room (32°C) and field-relevant (250°C) temperatures under true triaxial compression conditions. The failure behavior and fracturing plane were studied using acoustic emission (AE) testing, μm-scale computed tomography (μm-CT), and scanning electronic microscopy (SEM), in addition to the monitoring and analyses of pressure-flow curve during fracturing. The results show that (1) at the macroscale, the strength of the granite sample was weakened at high (field-relevant) temperature, as shown by a decrease in the breakdown pressure and increase in closure pressure from the pressure-flow curve; (2) at the microscale, the failure pattern of grains during fracturing did not differ much at high and room temperatures for both intergranular and transgranular fractures; and (3) due to upscaling issues from the laboratory to field, however, the laboratory experiment will not directly provide some critical parameters (e.g., mud window pressure needed for fracture initiation and borehole failure avoidance) needed for an EGS field exploration.